Asssessment of some selected vitamin levels in patients with vesico - vaginal fistula in Jos, Northern Nigeria. (International Journal of Medical and Surgical Sciences, 2017)
Globally, about 3.5 million women are living with genitourinary fistula, a miserable condition. Obstetric Vesicovaginal fistula (VVF) is exceptionally rare in developed part of the world, where it is mostly due to gynaecological cause. The study was conducted to provide baseline data on vitamin A and vitamin E levels among Vesico - Vaginal Fistula (VVF) patients and to establish their socio-demographic characteristics. Some selected vitamin levels in patients with Vesico - Vaginal Fistula (VVF) in Jos, Northern Nigeria were investigated using spectrophotometric method. Samples were collected from VVF patients undergoing treatments at the Evangel Hospital, Jos and the controls were non pregnant but parous women of similar social status who were willing to participate in the study. A total of 97 participants made up of 67 VVF patients and 30 controls were involved in the study. The results revealed that only 1 clients (1.49%) was mulliparous, 50 (74.64%) and 16 (23.88%) clients were multiparous and grand multiparous respectively out of 67 (100%) clients. The results of social class distribution in both clients and control is in the order of 5>4>3, 2>1. The levels of vitamin A in VVF clients showed no significant change (p>0.05) when compared to control while that of vitamin E showed significant change (p